Genomic and Transcriptomic Analyses Reveal Pathways and Genes Associated With Brittle Stalk Phenotype in Maize - Liu, Jun; Sun, Chuanbo; Guo, Siqi; Yin, Xiaohong; Yuan, Yuling; Fan, Bing; Lv, Qingxue; Cai, Xinru; Zhong, Yi; Xia, Yuanfeng; Dong, Xiaomei; Guo, Zhifu; et al. (Frontiers in Plant Science, 2022)
Mechanical strength of stalk affects the lodging resistance and digestibility of stalk in maize. The molecular mechanisms regulating brittleness of stalks in maize remain undefined. Here, we constructed a maize brittle stalk mutant (bk5) by crossing the W22::Mu line with the Zheng 58 line. The brittle phenotype of the mutant bk5 existed in all of the plant organs after the five-leaf stage. Compared to WT plants, the sclerenchyma cells of bk5 stalks had looser cell arrangement and thinner cell wall. Determination of cell wall composition showed that obvious difference in cellulose content, lignin content, starch content, and total soluble sugar were found between bk5 and WT stalks. Further, we identified 226 DEGs with 164 genes significantly up-regulated and 62 significantly down-regulated in RNA-seq analysis. Some pathways related to the cellulose and lignin synthesis such as endocytosis and glycosylphosphatidylinositol (GPI)-anchor biosynthesis were identified by KEGG and GO analysis. In BSA-seq analysis, we detected 2,931,692 high-quality SNPs and identified five overlapped regions (11.2 Mb) containing 17 candidate genes with missense mutations or premature termination codons using the SNP-Index methods. These genes were involved in the cellulose synthesis-related genes such as ENTH/ANTH/VHS superfamily protein gene (endocytosis-related gene) and the lignin synthesis-related genes such as cytochrome p450 gene. Some of these candidate genes identified from BSA-seq also existed differential expression in RNA-seq analysis. These findings increase our understanding of the molecular mechanisms regulating the brittle stalk phenotype in maize.